Analisis Pemasaran Industri Rumah Tangga Telur Asin Mekarsari Kecamatan Sumbersari Kabupaten Jember - Agustin, Fira; Yasin, Mochammad (KUBIS, 2023)
From a marketing perspective, the Mekarsari salted egg home industry is believed to have found a market gap, but it is not known where the owner sells salted eggs, whether it has a good level of efficiency, and what kind of marketing strategy is suitable for advancing its business. Research Objectives: To find out marketing channels, the level of marketing channel efficiency, and its marketing strategy in the Mekarsari salted egg home industry in Sumbersari sub-district, Jember district. The research method used descriptive qualitative analysis, and data analysis by observation, interviews, and questionnaires. The results showed that there were 3 marketing channel patterns for Mekarsari salted eggs, namely marketing channel I from producers to resellers (sales) to consumers, marketing channel II from producers to catering (housewives and food stalls) to consumers, marketing channel III from producers directly to consumers. And marketing channel I is very efficient because the efficiency value is 3.33%.Meanwhile, the results of the TOWS analysis obtained four alternative strategies consisting of SO, ST, WO, WT strategies. It can be concluded in the Grand Strategy matrix, the alternative strategies mentioned include the in the categories of market penetration strategy, market development, or product development.